Ramadan and Eid - Khan, Saniyasnain (Ajman,U.A.E Iqra book Distribution, 2024)
A splendid gift for your little ones this Ramadan. Ramadan and Eid gently introduces little children to the blessed month of Ramadan. Through simple and engaging text and beautiful illustrations, youngsters are presented with some of the important concepts of the Quran$1 (Bsuch as patience, tolerance, kindness and thankfulness.s
Keywords: Islamic Book